PENGARUH KUALITAS PRODUK DAN LOKASI TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA DISTRO BANDUNG CLOTHING SITUBONDO - Hidayatullah, Muhammad Arya; Soeliha, Siti; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of the study was to determine the effect of product quality and location on consumer satisfaction through purchase decisions as an intervening variable in Bandung Clothing Distro Situbondo. The sampling technique used in this study was simple random sampling with the Slovin formula with a tolerable error rate of 10% as many as 86 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product quality has a positive and significant effect on purchasing decisions, location has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on consumer satisfaction, location has a positive and significant effect on consumer satisfaction , Purchase decisions have a positive and significant effect on consumer satisfaction, product quality has a positive but not significant effect on consumer satisfaction through purchasing decisions, location has a positive and significant effect on consumer satisfaction through purchasing decisions.